Preparation of tobacco pyrolysis liquids in subcritical/supercritical ethanol and their application in the aroma enhancement of heated cigarettes - Zhao, Xuebin; Zhao, Shengchen; Xu, Yongming; Xu, Heng; Zhang, Zhan; Tian, Haiying; He, Qiang; Ma, Shengtao; Gao, Beibei; Ma, Chengjie (Frontiers in Chemistry, 2024)
For the aroma enhancement research of heated cigarettes, it is worth exploring whether tobacco can be pyrolyzed into pyrolysis liquids containing a large number of volatile aroma components. In this study, tobacco pyrolysis liquids were prepared in subcritical/supercritical ethanol, and their applications in the aroma enhancement of heated cigarettes were investigated. The optimal conditions of supercritical liquefaction reactions were determined by optimizing the reaction time, liquid/solid mass ratio and temperature conditions. Moreover, the effect of supercritical liquefaction conditions on volatile aroma components in tobacco pyrolysis liquids was investigated by GC-MS. The results indicated that the reaction temperature had the most significant impact on the tobacco pyrolysis reaction, and higher reaction temperature promoted the pyrolysis conversion of tobacco, resulting in enhanced tobacco conversion and a high content of volatile components in the tobacco pyrolysis liquid. The optimal reaction conditions for the preparation of tobacco pyrolysis liquid were found to be a temperature of 220°C, a liquid/solid mass ratio = 15, and a 2-h reaction time. Meanwhile, the content of ester compounds and nicotine in the tobacco pyrolysis liquid increased significantly with the increase of reaction temperature. Sub/supercritical ethanol treatment significantly destroyed the surface structure of tobacco, and the degree of tobacco depolymerization increased when temperature rised. The analysis of aroma compounds in the smoke of heated cigarettes indicated that the tobacco pyrolysis liquid could significantly increase the release of aromatic substances and has a significant aroma-enhancing effect. This article proposed and prepared tobacco pyrolysis liquid in subcritical/supercritical ethanol and explored its potential application in the aroma enhancement of heated cigarettes, offering a new route for flavor enhancement technology for this type of product.